Educational thought KH. Abdurrahman Ambo Dalle in the World of Education - Muhammad Ilham; Corry Iriani R; Nur Aeni Marta (Budapest International Research and Critics University, 2022)
The research objective is to analyze educational thought KH. Abdurrahman Ambo Dalle in the world of education. This type of research and analysis method in this study uses a qualitative approach in understanding educational thought KH. Abdurrahman Ambo Dalle in the world of education. The results show that educational thinking in the view of KH. Abdurrahman Ambo Dalle several factors including education is a way to get closer to Allah subhanahu wata'ala, education is a way to raise ignorance in society, and education as a form of concern for the condition of the indigenous people who were in conflict with the Dutch colonials.